Non-invasive F-actin visualization in living plant cells using a GFP mouse talin fusion protein - Kost, Benedikt; Spielhofer, Pius; Mathur, Jaideep; Dong, Chun-Hai; Chua, Nam-Hai (Actin: a dynamic framework for multiple plant cell functions, 2000)
The actin cytoskeleton has essential functions in the survival, the division, the growth and the morphogenesis of plant cells, and in the development of plant organs. A key approach to investigating these functions is the observation of the organization and the dynamic behavior of filamentous actin structures in plants cells. Visualizing plant actin filaments has been notoriously difficult, because they are highly sensitive to standard fixation and cell permeabilization procedures. This chapter demonstrates that the expression in plant cells of an optimized mutant version of the green fluorescent protein (GFP) from Aequorea victoria fused to the well characterized F-actin binding domain of mouse talin labels the actin cytoskeleton and allows non-invasive observation of its dynamic organization by fluorescence microscopy.
Keywords: actin visualization; GFP; mouse talin I/LWEQ domain